Beethoven's home in Heiligenstadt - Moll, Carl, 1861-1945 (artist):::Creator::::::::::::
Photogravure of painting of Beethoven's home in Heiligenstadt (Herrengasse 13, now Probusgasse 6) by Carl Moll.